Bilateral Striopallidodentate Calcinosis in Female: A case report - Kadel, Arun; Chandra, Avinash; Rajbhandari, Reema; Shrestha, Pranaya; Rajbhandari, Pravesh (Annapurna Journal of Health Sciences, 2023)
Bilateral striopallidodentate calcinosis (BSPDC) is associated with many neurological and psychiatric abnormalities and most commonly present with extra pyramidal symptoms and can be idiopathic or associated with endocrinopathy, frequently with parathyroid disorders. Here we describe a case who presented with generalized seizure. During workup, the cause of seizure was found to be bilateral and symmetric, extensive, irregular, intraparenchymal calcifications involving the basal ganglia, thalamus and dentate nucleus, white matter in the frontal, parietal, and occipital lobes and dentate nuclei of cerebellum. On the basis of clinical features, investigations, and exclusion of other causes of intracranial calcification a clinical diagnosis of BSPDC was made. BSPDC should be considered in the differential diagnosis of endocrinopathy particularly parathyroid disorders, when associated with neurological and psychiatric abnormalities.